Cellular evolution in the green algae / volvocales, tetrasporales and chlorococcales / Jeremy Pickett-Heaps and Julianne Pickett-Heaps. - Pickett-Heaps, Jeremy D.; Pickett-Heaps, Julianne (Ascot Vale, Vic., Australia : Cytographics Pty. Ltd. ; Sunderland, MA, USA : Sinauer Assoc. [distributor], 1995)
"This video disc offers teachers and students a dynamic view of evolution from simple to increasingly complex organisms."
"A Cytographics production."
Keywords: Green algae; Algae